Enviromental Sustainability Practices In The F&B Industry In Indonesia (Jurnal Riset Manajemen dan Akuntansi, 2025)
Food and beverage (F&B) businesses in Indonesia have experienced rapid growth, but this expansion has come with environmental challenges such as waste and carbon emissions. This study aims to explore how consumer perception, product innovation, and moral responsibility influence environmental sustainability, with environmental awareness as a mediating variable, using the Norm Activation Model (NAM) as the theoretical framework. A quantitative approach was employed using a descriptive-verificative method. Data were collected through an online questionnaire distributed to 150 respondents who had consumed environmentally friendly F&B products. Path analysis results show that consumer perception, product innovation, and moral responsibility significantly influence sustainable consumption behavior. Product innovation and moral responsibility were found to affect sustainability through the mediation of environmental awareness, whereas consumer perception has a direct effect without mediation. These findings reinforce the important role of environmental awareness in activating personal norms and support sustainability communication strategies in the F&B industry. The practical implications of this study encourage companies to enhance green product innovation and consumer education to promote more environmentally responsible consumption behavior.